IMPROVING LISTENING COMPREHENSION THROUGH BIOGRAPHY MOVIE AMONG YEAR ELEVEN STUDENTS - Taufiqurrahman, .; Salam, Urai; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The purpose of this research is to solve students? problem in improving listening comprehension, particularly their ability in comprehending specific information and identifying words from listening materials. Moreover, this research is intended to find out how does biography movie can improve the listening comprehension to the year eleven students of SMA Mujahidin Pontianak in academic year 2012 ? 2013. The method used in this research is classroom action research in which the researcher concerned with the improvement of students? listening comprehension in every meeting. This research was conducted in three cycles which consist of one meeting each. In collecting the data, the researcher used achievement test, field notes and observation sheets. The performance test which was used in this research was kind of listening test. The researcher then used scoring rubric to score the students? achievement in listening test. The observation sheets were used to collect qualitative data which was everything happened in teaching and learning process. The improvement of students? listening comprehension could be seen from the result of every meeting. Keywords:  Listening Comprehension, Biography Movie, CAR, Classroom Action Research Abstrak: Tujuan dari riset ini adalah untuk mengatasi permasalahan siswa dalam peningkatan pemahaman mendengarkan, khususnya kemampuan mereka dalam memahami informasi secara spesifik dan mengidentifikasi kata-kata dari materi listening. Lebih lanjut, riset ini ditujukan untuk mengetahui bagaimana kisah biografi dapat meningkatkan pemahaman mendengarkan terhadap siswa kelas sebelas di SMA Mujahidin Pontianak tahun ajaran 2012 ? 2013. Metode yang digunakan di dalam riset ini adalah penelitian tindakan kelas dimana fokus peneliti di sini yaitu peningkatan pemahaman mendengarkan siswa pada setiap pertemuan. Riset ini telah dilaksanakan dalam tiga tahap terdiri dari satu pertemuan di setiap tahap. Dalam pengumpulan data, peneliti menggunakan achievement test, lembar catatan dan lembar observasi. Tes kinerja yang digunakan di dalam riset ini adalah tes mendengarkan. Peneliti kemudian menggunakan rubrik penilaian untuk menilai pencapaian siswa dalam tes mendengarkan. Lembar observasi digunakan untuk mengumpulkan data kualitatif yang terjadi selama proses belajar mengajar. Peningkatan pemahaman mendengarkan siswa dapat terlihat dari hasil yang diraih dari setiap pertemuan. Kata kunci: Pemahaman Mendengarkan, Kisah Biografi, RTK, Riset Tindakan Kelas